Masyarakat Yei-Nan di Erambu dan Ritus Kematiannya: Studi Kasus untuk Menemukan Makna Ritus Kematian dalam Masyarakat Yei-Nan di Erambu, Kabupaten Merauke – Papua - Pegan, Maximilian Boas (Studi Budaya Nusantara, 2017)
ABSTRACT The Yei-nan are a small tribe inhabiting the east mostregion of Indonesia. They posess a culture rich in both spiritual and mundane values, these distinct teachings influence all aspects of life, from birth until the passing away of tribe members. Common the most Melanesian cultures, the Yei-nan also have numerous rituals concerning mortality. The ritual centered upon the belief that the mourning family may aid in sending the deceased to the afterlife or spirit world. However this is not the sole purpose, undeniably these elaborate rituals also serve to re-strengthen the ties between man, fellow members, nature and the spirit realm.